Urban Governance Management Towards Managing Slum Area in Indonesian Cities - Adil Faisal Alwini; Herdis Herdiansyah (Matra Pembaruan: Jurnal Inovasi Kebijakan, 2018)
The population growth of a city from time to time experiences rapid development. This situation leads to socio-economic and cultural changes and have an impact on their interactions with other cities and the surrounding area. The rise of economic growth in big cities has made the pace of city development faster, making housing demand higher. That way, land use is increasingly competitive. The problem then creates a slum area. The challenges and obstacles that will be faced in the effort to deal with slums are the unavailability of accurate data and information in each region, which can inform the slums that can be adequately handled. For this reason, the purpose of this research is to find out the governance of urban slums. The research used is descriptive qualitative and uses AHP Method. The results of the study reveal several slum typologies such as the concept of rigid environmental structuring, lack of drinking water supplies, etc. The research also discusses government practices, as well as prevention of slum areas in urban areas. This research concludes the need for accurate database and information in each region to deal with slum areas in the city, as well as accurate information about handling the slums